Eastern Europe in Revolution - Banac, Ivo (Cornell University Press, 2019)
In this book twelve outstanding authorities present their thoroughgoing assessments of the East European revolution of 1989-the definite collapse of communism as an ideology, a political movement, and a system of power in eight countries. All but two of the contributors focus on the revolution in an individual region or country-Poland, Hungary, the German Democratic Republic, Czechoslovakia, Romania, Bulgaria, Yugoslavia, and Albania-and each of them addresses the theme of regime transition. In Eastern Europe, of course, the transition from communism to ... has been as complex and varied as the political geography of the notorious "fracture zone" itself, and individual authors thus concentrate on different sets of problems; they tell different kinds of stories. Pointing to the enormous difficulties of systematic transformation, they measure the dangers of nationality conflict and the potential for new authoritarianism. Ivo Banac has assembled a cast with impressive credentials. Without imposing an artificial unity on a chaotic subject, their book maps out the events of 1989-90 and sets the background for figuring out where the region may be headed.